Ethosome: A nanocarrier for transdermal drug delivery - Razavi, Hamideh; Janfaza, Sajjad (Archives of Advances in Biosciences, 2015)
Ethosomes are a novel and alternative drug delivery systems and currently the focus of many research activities. Ethosomes are soft, flexible vesicles that are composed mainly of phospholipids, ethanol and water. Ethosomes can provide better skin permeation than liposomes and deliver enhanced amounts of both small and large therapeutic agents through skin and targeting to deeper skin layers for various diseases. Finally deliver to the systemic circulation. It is clear that ethosomal carrier because of presences ethanol cause skin disruption and increases lipid fluidity. In this review, the mechanism of penetration, applications, preparation, advantages and disadvantages of ethosomes are illuminated.